Dose-response relationship between lipids and all-cause mortality in the dialysis population: a meta-analysis - Ye Yao; Jing Xiong; Mi-Yuan Wang (BMC Nephrology)
Abstract Background The use of lipid-lowering drugs in the dialysis population has been controversial and there is no target for the dialysis population. Objectives To elucidate the dose-response relationship between lipids and all-cause mortality in the dialysis population. Methods Computer searches of PubMed, Embase, Web of Science, CNKI, and Wanfang. Data were conducted to collect published cohort studies on lipids and all-cause mortality in the dialysis population from home and abroad up to February 2023. Meta-analysis was applied to calculate the combined effect size (Hazard ratio) and its 95% confidence interval and dose-response relationship by applying Stata17.0. Results A total of 11 publications with a cumulative total of 106,808 individuals were included. All-cause mortality was statistically different between the highest dose total cholesterol (TC) group and the low TC group (HR = 0.82, 95% CI = 0.75–0.90, P < 0.05). The TC range for lower all-cause mortality is > 140.5 mg/dL, and on this basis, TC in the range of 180–220 mg/dL may have a better prognosis for dialysis population. There was a nonlinear relationship between Non-high-density lipoprotein cholesterol (NHDL-C) cholesterol and all-cause mortality, with no statistical difference between the high and low dose group. In contrast, Low-density lipoprotein cholesterol (LDL-C) masked its association with all-cause mortality due to changes in death spectrum, differences in relative time risks, and other factors. In the 50–450 mg/dL range, all-cause mortality in the dialysis population was positively associated with triglycerides (TG), with a 2.5% increase in all-cause mortality per 50 mg/dL increase in TG (HR = 1.025, 95% CI = 1.003–1.048, P = 0.01). Conclusion TC is a target for monitoring the dialysis population, which has the lowest all-cause mortality in the range of 180–220 mg/dL. However, NHDL-C and LDL-C monitoring is not clinically meaningful. Increased TG can contribute to the risk of higher all-cause mortality in dialysis patients.